Assessment of mediating effect of indigenous oil firms' participation on the relationship between local content policy and job creation - Niran, Adedeji Abdulkabir; Ahmad Sidique, Shaufique Fahmi; Abd Rahman, Azmawani (2015)
The primary target of the local content policy (LC policy) introduced into the Nigerian oil and gas sector is to address the issue of increasing value-added to the local economy. Specifically, the policy often aimed to increase participation of indigenous oil firms in supply service activities in the sector through which more jobs could be created for the citizens. Thus, this paper assesses the mediating effect of indigenous oil firms’ participation on the relationship between LC policy and job creation in Nigeria’s oil sector. Data were obtained through the self administered questionnaires survey from the Nigeria indigenous oil service firms.The bootstrap technique in Partial Least Squares Path Modeling (PLS-PM) was applied for the analysis. The bootstrap procedure yielded a significant point estimate of 0.16, with BCa 95% confidence interval (CI) lies between 0.043 and 0.249. Since zero does not lie between these values, this suggests that indigenous oil firms’ participation has a significant mediating effect on the policy-job relationship. The implication is that LC policy may increase job creation within the industry if it increased indigenous oil firms’ participation.